Uji Efektivitas Jamur Beauveria bassiana dan Waktu Aplikasi Terhadap Hama Spodoptera litura Pada Tanaman Sawi Hijau (Brassica juncea) - Alum Turnip; Dirk Y.P. Runtuboi; Daniel Lantang (Jurnal Biologi Papua, 2018)
Beauveria bassiana is one type of entomopathogenic fungi that can be used as a biopesticide. Papua province is rich in natural contents, as well as B. bassiana fungus isolated from soil rhizofir banana plants at the location Housing Cenderawasih University Lecturer Jayapura, Perumnas III Waena, Heram District, Jayapura, Papua Province. Local isolates of B. bassiana fungus reproduced in the Laboratory of Microbiology, Cenderawasih University Jayapura. This study aimed to get to get a concentration of B. bassiana fungus that effectively kill pests Spodoptera litura mustard greens (Brassica juncea), the time interval applications (morning, afternoon, and evening) B. bassiana fungus that effectively kill pests S. litura the mustard greens (B. juncea) and knowing the difference effectiveness of B. bassiana fungus concentration and application time (morning, afternoon, and evening) to pests S. litura green mustard (B. juncea) as well as the interaction fungus B. bassiana and application time (morning, afternoon and evening) to pests S. litura green mustard (B. juncea) with Randomized Complete Design Factorial (RAK-F) which consists of two factors: the concentration of fungi B. bassiana and time of application. The results obtained that the concentration of the fungus B. bassiana were effectively kill pests S. litura is a concentration of 1 % and 1.5 %. The time interval B. bassiana fungus that effectively kill pests S. litura is morning, afternoon and evening. Differences in the effectiveness of the fungus B. bassiana and applications in the time interval kill pests S. litura is a concentration of 0.5 % and 1.5 % in the morning, afternoon, and evening. Interval time of application of the interactions of fungi   B. bassiana in killing pests S. litura is an afternoon with a concentration of 1.5 % on day 5 by 5 %, the 8th day amounted to 17.5 %, the 11th day amounted to 32.5 % and on day-14 amounted to 42.5 %.  Key words: B. bassiana, B. juncea, effectiveness, time applications.